2019
DOI: 10.19044/esj.2019.v15n9p263
|View full text |Cite
|
Sign up to set email alerts
|

Diversité des Espèces de Faunes Chassées et Impact sur la Biodiversité Animale (Nord-Ouest du Bénin)

Abstract: La chasse est une activité importante pour les communautés proches des réserves de faunes malgré ses impacts négatifs sur les espèces sauvages. Durant un an et demi, un suivi quotidien a été mené aux côtés des chasseurs pendant 203 parties de chasse dans la zone d'étude. L'objectif de cette étude était de recenser les espèces chassées, d'analyser les différents lieux des prélèvements et d'évaluer la pression subie par la faune. L'utilisation des Modèles Linéaires Généralisés réalisés avec le logiciel R 3.4.1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 19 publications
0
7
0
4
Order By: Relevance
“…The results of Chabi-Boni et al [22] , Djagoun et al [25] and Zangada et al [46] confirmed that some species, despite anthropogenic pressures, show a preference for more or less anthropised habitats. Some respondents revealed that certain species are captured in large numbers in anthropised environments rather than in protected environments, as revealed by the results of Chabi-Boni et al [22] . This may be due to the fact that the core area is protected and hunters have difficulty hunting there because of surveillance patrols.…”
Section: Identification Of Species Hunted In the Lama Forest Reservementioning
confidence: 91%
See 4 more Smart Citations
“…The results of Chabi-Boni et al [22] , Djagoun et al [25] and Zangada et al [46] confirmed that some species, despite anthropogenic pressures, show a preference for more or less anthropised habitats. Some respondents revealed that certain species are captured in large numbers in anthropised environments rather than in protected environments, as revealed by the results of Chabi-Boni et al [22] . This may be due to the fact that the core area is protected and hunters have difficulty hunting there because of surveillance patrols.…”
Section: Identification Of Species Hunted In the Lama Forest Reservementioning
confidence: 91%
“…In the ephemeral pools of the Central Nucleus, the presence of Catfish (Clarias gariepinus) and probably endemic Cyprinodontidae [28] is mentionned. With regard to insects, ninety-three (93) species of butterfly have been noted in the Lama Forest Reserve, thirty-eight (38) of which are infested with forest areas, twenty-two (22) with savannahs and 18 are considered ubiquitous. The central core of the Lama Forest Reserve contributes considerably to the specific wealth of termites and lepidoptera in South of Benin.…”
Section: Wildlife Diversity and Human Resourcesmentioning
confidence: 99%
See 3 more Smart Citations